2014
DOI: 10.1016/j.infbeh.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mothers who are securely attached in pregnancy show more attuned infant mirroring 7 months postpartum

Abstract: This study contrasted two forms of mother-infant mirroring: the mother's imitation of the infant's facial, gestural, or vocal behavior (i.e., “direct mirroring”) and the mother's ostensive verbalization of the infant's internal state, marked as distinct from the infant's experience (i.e., “intention mirroring”). Fifty mothers completed the Adult Attachment Interview during the third trimester of pregnancy. Mothers returned with their infants 7 months postpartum and completed a modified still-face procedure. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 97 publications
(131 reference statements)
0
18
0
1
Order By: Relevance
“…Mothers from this attachment group also show reduced activation of the mesocorticolimbic DA system, including the ventral striatum and ventromedial PFC, when viewing images of their own versus unknown infants’ faces (Strathearn et al, 2009a). Furthermore, this pattern of attachment is associated with differences in maternal behavior, including less attuned mother-to-infant vocalization at seven months postpartum (Kim et al, 2014), and with higher rates of insecure child attachment at 14 months, based on the Strange Situation Procedure (Shah et al, 2010). …”
Section: Postpartum Factors Of Maternal Brain Plasticitymentioning
confidence: 99%
“…Mothers from this attachment group also show reduced activation of the mesocorticolimbic DA system, including the ventral striatum and ventromedial PFC, when viewing images of their own versus unknown infants’ faces (Strathearn et al, 2009a). Furthermore, this pattern of attachment is associated with differences in maternal behavior, including less attuned mother-to-infant vocalization at seven months postpartum (Kim et al, 2014), and with higher rates of insecure child attachment at 14 months, based on the Strange Situation Procedure (Shah et al, 2010). …”
Section: Postpartum Factors Of Maternal Brain Plasticitymentioning
confidence: 99%
“…In non-human primates, repeated births are accompanied by an increase in caregiving and a decrease in neglect and abusive behaviors (Ruppenthal et al, 1976). In women, whereas the effects of parenthood on neural activation has received recent attention, most of the studies have focused on the activation of neural regions during active motherhood and less so on the potential long-term changes in neural activation associated with a prior parity (Strathearn, 2011; Kim et al, 2014). However, in a couple of studies using fMRI the effects of prior reproductive experience have been measured to examine possible changes in neural activation between first time and experienced mothers (Swain et al, 2007; 2011).…”
Section: Behavioral Consequences Of Reproductive Experiencementioning
confidence: 99%
“…Profound early deprivation, as was seen in Romanian institutional rearing, has been observed to lead to severe long‐term attachment disturbances and social deficits . The developmental literature is replete with decades of prospective longitudinal and cross‐sectional studies linking early trauma and/or disrupted attachment to long‐term social and attachment dysfunctions . There has been an increasing number of studies linking these social deficits to compromised OT functions …”
Section: Oxytocin Systemmentioning
confidence: 99%
“…89,90 The developmental literature is replete with decades of prospective longitudinal and cross-sectional studies linking early trauma and/or disrupted attachment to long-term social and attachment dysfunctions. [91][92][93][94] There has been an increasing number of studies linking these social deficits to compromised OT functions. 57,95,96 Recent advances in neuroscience have revealed that there may be a significant overlap in the neurobiological mechanisms that underpin social attachment and addiction.…”
Section: Behavioral Levelmentioning
confidence: 99%